Evaluasi Penilaian Kinerja Dalam Klasifikasi Data Mining Dengan Metode Naive Bayes - Romli, Ikhsan; Putra, Boy Manggala (DPPM UNIVERSITAS PELITA BANGSA, 2020)
Performance appraisal evaluation is necessary to evaluate the work results of employees in a company. The company certainly has a standard employee assessment from various aspects, starting from performance results, appearance and personality. PT. Berkat Sinar Sentosa is a company engaged in the provision of security services, office boys and drivers. However, it is very unfortunate because the company is still manual in evaluating security performance assessments, so that decision making in determining competent and incompetent security cannot be said to be effective and efficient. In this study, an evaluation of the security performance of PT. Thanks to Sinar Sentosa, the PT. Panin Bank Tbk Kcu Pecenongan with the aim of knowing the accuracy in classifying competent security and incompetent security. The data used in this study used 63 training data without using test data, but still in the form of test sample data as a reference for calculating naïve Bayes. This test is performed using the Naïve Bayes data mining algorithm and the Rapid Miner Framework. From calculations using the Naïve Bayes algorithm, the accuracy is 85.71%, precission is 88.24% and recall is 85.71%.